Peranan Visum Et Repertum dalam Proses Pembuktian Perkara Pidana Penganiayaan Biasa yang Mengakibatkan Kematian (Putusan Nomor: 3490/Pid.B/2015/Pn.Mdn) - Shara, Desi Wilma; Amelia, Nikita Rizky; Manalu, Buana Raja (Universitas Medan Area, 2019)
The investigation of a criminal offence case in the court generally is to find out the material real truth from a criminal offence case.The effort from the legal side (state enforcers) is to get evidences from a case processed.In criminal case investigations should have an evidence that strongly appoints the fault of the suspect. A persecution case needs an expert description to strenghten the persecution case and to be reported into Visum Et Repertum whether the persecution effects is afterwards deaths (ie hospital) or murder.This research is based on court case number 3490/Pid.b/PN.Mdn.The purposes of the research is to find out the causes of persecution occurences and to know what is the role of the Visum Et Repertum in proofing the persecution case that caused the death.